Pengangguran dalam Perspektif Ekonomi Islam dan Kovensional: Pengertian, Sebab, dan Solusi - Akhmal Choirul Amar; Garnes Puji Astuti; Iqbal Fathoni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses one of the employment problems in Indonesia, namely unemployment. This relates to employment management, including conventional and sharia (Islamic) components. The economic and social aspects of people's lives are greatly influenced by where they work. In a sharia (Islamic) perspective, employment and unemployment are aspects of employment issues with certain ethical and moral guidelines. This article discusses and investigates conventional and sharia perspectives on the problem of unemployment, including its definition, causes, solutions and implications for the Indonesian labor market. Researchers used qualitative techniques and library research data to write this article.